Design, Management and Key Success Factors of an Offshore Cathodic Protection System for Corrosion Control - Shobhendu Prabhakar; Gaurav Goswami (International Journal of Engineering and Management Research, 2019)
Corrosion is a very prevalent issue for offshore operations in the oil and gas industry. If the corrosion issues are not addressed adequately, these may lead to quality failures, safety incidents, compromise to asset integrity and high inspection costs. This research paper discusses and analyzes corrosion types, corrosion threats, mechanisms to protect against corrosion, design and management of cathodic protection system, and key success factors for a cathodic protection system for an offshore oil and gas production system.